2016
DOI: 10.1007/s11136-016-1400-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of a dyadic psycho-educational intervention on caregiver burden and morbidity in partners of patients with heart failure: a randomized controlled trial

Abstract: NCT02398799.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 59 publications
1
35
0
17
Order By: Relevance
“…However, most of them reported neglecting their needs, so it might be possible that some of them are not even aware of their actual needs and possibilities for support in the healthcare or community setting. We believe that offering a supportive environment and facilitating discussion and sharing problems in education for HF patients and informal caregivers could further support their ability to deal with HF and enhance their quality of life [44]. Healthcare professionals also recognized patients' and informal caregivers' need for psychosocial support and emphasized that efforts to offer them support in the community setting should be made in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them reported neglecting their needs, so it might be possible that some of them are not even aware of their actual needs and possibilities for support in the healthcare or community setting. We believe that offering a supportive environment and facilitating discussion and sharing problems in education for HF patients and informal caregivers could further support their ability to deal with HF and enhance their quality of life [44]. Healthcare professionals also recognized patients' and informal caregivers' need for psychosocial support and emphasized that efforts to offer them support in the community setting should be made in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial found that the load and negative health effects did not significantly decrease after a follow-up program of relatives of patients with heart disease. Mapping relatives’ initial experiences may also provide a better customized follow-up program 44. This emphasizes the importance of both early and adapted support for relatives 34.…”
Section: Discussionmentioning
confidence: 99%
“…(Schwarz et al, 2008) In the five papers which reported secondary outcomes or primary outcome variables at a later time null findings were noted. (Agren et al, 2013;Agren et al, 2015;Liljeroos et al, 2015Liljeroos et al, , 2016Liljeroos, Agren, Jaarsma, & Stromberg, 2014a) These included outcomes such as quality adjusted life years, (Agren et al, 2013) carer tasks, burden or patient morbidity, Liljeroos et al, 2016) or non-sustaining differences at a subsequent measurement time. (Liljeroos et al, 2015;Liljeroos et al, 2014a) Deeper analysis identified perceived control, quality of life, preparedness to care, self-care, depression, social support and rehospitalization as the outcome variables with mixed (positive and null) findings (Table 3).…”
Section: Affective Outcomesmentioning
confidence: 99%